Human Rights in the Criminal Justice System in Indonesia - Firayani`, Firayani (PT. Anagata Sembagi Education, 2024)
Human Rights (HAM) are basic rights inherent in every individual and are universally recognized. In the Indonesian context, human rights protection is an integral part of the national legal system, especially in the criminal justice system. However, the implementation of human rights in the Indonesian criminal justice system often faces various challenges, ranging from acts of torture, unfair treatment, to violations of the rights of suspects or defendants. This article aims to analyze the extent to which human rights principles are applied in the criminal justice process in Indonesia, as well as to identify inhibiting factors and reform efforts that have been and need to be carried out. Through a qualitative approach, this article examines various laws and regulations, case studies, and expert opinions to provide a comprehensive understanding of the integration of human rights in the criminal justice system. The results of this study are expected to be an academic contribution in encouraging the realization of a legal system that is fair, humane, and respects the dignity of every individual.